PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN PADA SISWA KELAS V SD NEGERI KESTALAN NO.05 SURAKARTA - Risa Sulistyaningsih; Mukhlis Mustofa (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract: The problem in this research is the low student learning outcomes in mathematics. This type of research is classroom action research through the role of learning video media. The purpose of this study was to determine: (1) an overview of the use of video media for learning mathematics, (2) a description of student learning outcomes, (3) the effect of using video media for learning mathematics on students' interest and learning outcomes. The research subjects were teachers and students of class VA of SD NegeriKestalan No.05 Surakarta in the academic year 2021/2022, with 28 students consisting of 12 boys and 16 girls. The results of the study showed that it could improve the mathematics learning outcomes of 5A grade students of SD NegeriKestalan No.05 Surakarta. This can be seen from before the action was taken, namely in the pre-cycle only 12 students or 43% completed, in the first cycle increased to 15 students or 54% who completed  learning mathematics and in the second cycle increased again to 25 students who completed learning mathematics or 89 %. Keywords: learning outcomes, learning video media, mathematics Abstrak:Permasalahan dalam penelitian ini adalah rendahnya hasil belajar siswa pada mata pelajaran matematika. Jenis penelitian ini adalah penelitian tindakan kelas melalui peranan media video pembelajaran. Tujuan penelitian ini yaitu untuk mengetahui : (1) gambaran penggunaan media video pembelajaran matematika siswa, (2) gambaran hasil belajar siswa, (3) Pengaruh penggunaan  media video pembelajaran Matematika terhadap minat dan hasil belajar siswa. Subyek penelitian yaitu guru dan peserta didik kelas VA SD Negeri Kestalan No.05 Surakarta tahun pelajaran 2021/2022,dengan junlah peserta didik 28 terdiri dari 12 laki-laki dan 16 perempuan. Hasil dari penelitian menunjukkan dapat meningkatkan hasil belajar matematika siswa kelas 5A SD Negeri Kestalan No.05 Surakarta. Hal ini dapat dilihat dari sebelum dilakukan tindakan yaitu pada pra siklus hanya 12 siswa atau 43% yang tuntas, pada siklus I meningkat menjadi 15 siswa atau 54% yang tuntas belajar matematika dan pada siklus II meningkat lagi menjadi 25 siswa yang tuntas belajar matematika atau 89% Kata kunci: hasil belajar, media video pembelajaran, matematika